Underway velocity measurements in the Alderney Race: towards a three-dimensional representation of tidal motions. (21st August 2020) - Sentchev, Alexei; Nguyen, Thinh Duc; Furgerot, Lucille; Bailly du Bois, Pascal
Abstract : The Alderney Race, located northwest of the Cotentin Peninsula (France), is a site with high tidal-stream energy potential. Circulation through the Alderney Race is complex, with current speed exceeding 3 m s −1 at neap tide. Towed acoustic Doppler current profiler (ADCP) measurements and static point velocity measurements were performed in July 2018 focusing on assessment of circulation and vertical structure of tidal currents. Transect surveys revealed peculiar features of local dynamics such as change in location of the tidal jet on ebb and flood flow. The spatial expanse of the tidal jet was quantified and regions with largely sheared or nearly homogeneous velocity distributions were identified on the cross-sections. Velocity profiles acquired along the cross-sections were accurately characterized using a power law. The spatial variability of the power-law exponent α was found to be large and correlated with the tidal conditions. The largest variation in profile shape was observed in the northern sector and assumed to be generated by the current interaction with a bathymetric constriction. The velocity profiles were found to vary from highly sheared on flood flow to nearly homogeneous on ebb flow, with corresponding range of power-law exponent α variation from 6 to 14. In the southern sector, over a relatively smooth bathymetry, the velocity profile shape was accurately approximated using the 1/7 power law with a range of variation of α from 6.5 to 8, with respect to the tidal conditions. To our knowledge, this is the largest field survey done using towed ADCP and the results could represent a significant advance in tidal site characterization and provide advanced information to turbine developers. This article is part of the theme issue 'New insights on tidal dynamics and tidal energy harvesting in the Alderney Race'.